Strategi Pemerintah Desa Sukosewu Dalam Mencegah Pekerja Migran Non Prosedural Melalui Program Desmigratif - Ratna Triwulandari; Iman Pasu Marganda Hadiarto Purba (Universitas Negeri Surabaya (Unesa), 2023)
Sukosewu Village is one of the pockets of migrant workers in Blitar who has problems with migrant workers. Non-procedural migrant workers are vulnerable to discrimination and criminalization due to their positions that are not in accordance with procedures. This research is important to study considering that the village is the main exit door for people to work abroad, so it is necessary to have a strategy to prevent non-procedural migrant workers from the village. This study uses John Middleton's Communication Strategy theory that the best communication are combinating all of element that consist of communicator and communican although media to achieve the goals. This research use case study methods refers to Robert K. Yin. Informan choosen by purposive sampling that consider by some chriteria. The research location is at the Sukosewu Village Office, Gandusari District, Blitar Regency. The data collection technique used is in-depth interviews related to the communication strategy carried out and documentation. The data research was analyzed using the opinions of Miles and Huberman combined with John Middleton's theory of communication strategy. The results of this study there are four strategies used, namely migration service strategies, personal approach strategies, social media monitoring strategies, and technical guidance strategies for community leaders. This program has been successful because there are no more non-procedural migrant workers from Sukosewu Village in the 2019-2021 departure year. There are factors that encourage and hinder the implementation of the Desmigratif Program in Sukosewu Village. Several things need to be done to overcome the inhibiting factors, among others, a personal approach, socialization of the Desmigratif Program and the creation of an attractive support program.Keywords: migrant workers, Desmigratif Programe, Village Government Strategy.